Gravesia gautieri (Melastomataceae: Sonerileae), a new species from northern Madagascar - Almeda, Frank; Pacifico, Ricardo (Phytotaxa, 2025)
Gravesia gautieri, a new species from northern Madagascar, is described, illustrated, mapped, and compared with presumed relatives based on morphological characters. It is readily diagnosed by its sparingly branched suffrutescent habit, 3-nerved leaf blades that are coarsely and remotely serrate at least distally with a sparse cover of minute brown granular hairs and ± appressed smooth hairs abaxially, long-pedunculate umbellate inflorescences, ± terete and ecostate hypanthia, obsolete calyx lobes with callose-thickened teeth borne on and barely exceeding the calyx tube in length, and dorso-basal subulate staminal appendages that are deflexed to variously coiled.